EFEKTIVITAS PENGENDALIAN INTERNAL PENJUALAN KREDIT RUMAH PADA PERUM PERUMNAS CABANG KALIMANTAN TIMUR - Paung, Yustiani Manasye (EKONOMIA, 2014)
The purpose of this paper is to investigate and analyze the control in the sale of home loans in East Kalimantan branch Perumnas.In accordance with the purposes of this study the main issues pointed out